The Effects of Some Essential Oils on Methicilin Resistant Staphylococcus aureus - Ali Soyuçok (Turkish Journal of Agriculture: Food Science and Technology)
Microbial contamination in food and medicine is a situation that closely concerns human health. The fact that the microorganism causing the contamination have antibiotic resistance makes it difficult to eliminate the contamination. Deficiencies such as incorrect use of antibiotics or lack of new antibiotics have caused microorganisms to acquire multiple antibiotic resistance. Methicillin-resistant S. aureus (MRSA) is one of the microorganisms with high antibiotic resistance. The antibiotic resistance mechanisms and biofilm production ability of MRSA has made it more resistant to the environment. In this study, disc diffusion method was used to determine the antimicrobial activities of Heracleum platytaenium and Lavandula spp. essential oils against MRSA, and the results were compared with commercial antibiotics. In addition, the effect of H. platytaenium and Lavandula spp. essential oils on the biofilm produced by MRSA was also investigated. In this study, it was determined that H. platytaenium and Lavandula spp. essential oils have antimicrobial activity against MRSA. It was found that H. platytaenium and Lavandula spp. essential oils have antibiofilm activity against MRSA. H. platytaenium and Lavandula spp essential oils can be alternative natural sources compared to commercial antibiotics in controlling infections from MRSA.